Test The Activity Of Administering Ethanol Extract Cream From Gambier Leaves (Uncaria Gambir Raxb) To Accelerate The Healing Of Incision Wounds On The Surface Of The Skin Of Male Wistar Strain Rats (Rattus Norvegicus) - Arif, Maria Nisaul; Amansyah , Adek; Suhartina, Suhartina (Sean Institute, 2023)
Wound healing, especially incisions, is still a problem in the health sector due to the many cases and treatment approaches used during globalization. This research tested whether ethanol extract cream from gambier leaves (Uncaria Gambir Raxb) could accelerate the healing of skin wounds in male Wistar rats. Pre-test and post-test with control group design were used in this laboratory experiment. In this study, the acceleration of healing was the dependent variable. Meanwhile, gambier leaf extract cream is an independent variable in the laboratory of the Faculty of Mathematics and Natural Sciences, University of North Sumatra. The research process has several stages: Rat acclimatization, Gambir Leaf Extract and Cream Formula, White Rat Incisions, Histopathological Observations, and Data Processing. SPSS 22 analyzes research data. Shapiro-Wilk determined data normality. One-way ANOVA calculated group mean differences for well-distributed data (P > 0.05). The Post Hockey (HSD) test detected significant treatment differences (P 0.05). The Kruskal-Walli test is used for irregular data. In white mice, 15% gambier leaf extract cream healed cuts better than 5% and 7.5%. However, gambier leaf extract cream 7.5% has a performance like 15%. At a concentration of 7.5%, secondary metabolite compounds from gambier leaf extract heal wounds, while low concentrations suppress bacteria, making them less effective. Thus, gambier leaf extract contains antioxidant phytochemicals that can be used as medicine.